Family agriculture and sustainable development: a characterization of the rural producer fair in the municipality of Marechal Cândido Rondon – Paraná, Brasil (Research, Society and Development, 2021)
Free trade fairs are important vectors for rural development in family agriculture, being a strategy to face difficulties related to commercialization. This research aims to characterize the rural farmer fair of Marechal Cândido Rondon/PR and provide a look at its potentialities and limitations. For this purpose, an interview was conducted with open and semi-open questions, applied to the president of the fair and twelve consumers. It was also used as a tool for the study, the Matrix FOFA (Strengths, Opportunities, Weaknesses, Threats) or SWOT Analysis (Strenghts, Weaknesses, Opportunities and Threats); and the Venn Diagram. The matrix analysis revealed that the organization of the fair is the main strength found, while the infrastructure is weakness. The fair has great opportunities, especially in its dissemination, however, presents the lack of support from Technical Assistance and Rural Extension agencies as the main threat. Although farmers are very satisfied with this short circuit commercialization model, there is a lack of investment by the local public power. The remarkable potential is the organizational process at the fair, and as a limitation there is a lack of effective dialogue between its board of directors and municipal bodies, a subject that can be investigated in future related studies. It is noted that investing in Marechal Cândido Rondon's free trade fair is to encourage not only family farmers who work on sales, but also to consolidate the importance of the class for the city's healthy food.